The capacity and capability of a low performing rustic primary school: establishing the groundwork / Bridget Lim Suk Han - Lim, Bridget Suk Han (Universiti Teknologi MARA, Cawangan Melaka, 2019)
The main purpose of this paper was to establish the initial groundwork for a larger ethnographic fieldwork case study so that the novice English teachers could be more prepared to face the peculiarities of rustic schools particularly the issue of the learning environment where they would be posted to. For the purpose of this paper, it focussed on only decontextualizing the data on climate and effectiveness factors to determine the capacity and capability of the school. Initial data revealed that English was the 'killer subject' for this case school where the Primary School Assessment Examination (UPSR) was concerned. These data were obtained through peripheral observations, formal and casual interviews, classroom participation as well as document analysis. The data from the study seemed to confirm the interrelationship of the climate and effectiveness factors to determine educational effectiveness of this low performing primary school. The descriptive qualitative data from the study allowed me as the researcher to interpret and comprehend the scenario to craft a detailed depiction of the teaching and learning of the English language in this rustic primary school. Hopefully, this would render a more holistic understanding not only on the feebleness and fortes of the school but more importantly on how novice English teachers as the initiators of the learning of the English language in the classroom could make more judicious decisions on how to uplift and improve academic performance among the pupils especially with regards to the teaching and learning of English language.